REPRODUCTIVE PERFORMANCE OF ANESTROUS NON-DESCRIPTIVE COWS TREATED WITH CIDR AND PGF2alpha - VIJAYARAJAN, A; MEENAKSHISUNDARAM, S (The Indian Journal of Animal Reproduction, 2023)
The present clinical study was carried out to evaluate the reproductive performance in non descriptive cowsusing (CIDR) and PGF2a under field condition. The cows were divided into two groups comprising of 12 cows ineach group. Group I animals (n= 12) served as control and were inseminated during natural estrus and in group IIcows (n= 12) estrous cycle was induced by inserting CIDR for9 days and PGF2a was given intramuscularly 24 hrsprior to CIDR removal. Fixed time artificial insemination was carried out at48 and 72 hrs after CIDR removal. Theoverall conception rate obtained was 41.66 % in group I animals and 91.66 % in group 11 animals treated with Cl DRand PGF2alpha.
Keywords: CIDR; PGF2alpha; Anestrous; Non descriptive cow; Reproductive Performance